SYNTHESIS AND CHARACTERIZATION OF IONIC LIQUID TEMPLATED MESOPOROUS SILICA NANOPARTICLES AS A DRUG CARRIER FOR IBUPROFEN AND QUERCETIN - RAMELI, NAJIHAH (2021)
The development of mesoporous silica nanoparticles (MSN) as a carrier for drug delivery was studied to overcome the limitation and improving oral bioavailability of poor water solubility. In this study, a series of MSN was successfully synthesized using different ionic liquids (ILs) as a template. Their versatile properties such as stability, tuneable physical characteristics, great biocompatibility make them suitable candidates for this approach. The synthesis of MSN typically involves solvents, silica precursor, acid or base as catalyst, and surfactant as templates. Currently, the most well-known template to generate MSNs are anionic surfactants like hexadecyltrimethylammonium bromide (CTAB). However, the recent discovery of ionic liquid (IL) has been the great potential as the alternative template materials for MSN other than anionic surfactant. Therefore, in this work ionic liquid templated MSN were synthesized to develop the drug delivery. This is due to the similar core structure of ILs with CTAB in which both consist of inorganic or organic anions and bulky organic cations. One of the advantages of ILs is the wide range of cations and anions that can be used to change their physical properties. Five ILs and a surfactant with different alkyl side chains and types of anions namely 1-dodecyl-3-methylimidazolium iodide ([C12mim][I]), 3-diethylamino propanol vanillate (DV), 2-butylamino ethanol salicylate (BS), 3-diethylamino propanol salicylate (DS), 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide ([bmim][NTf2]) and hexadecyltrimethylammonium bromide (CTAB) were used. The used ILs has diverse combination of cations and anions that can help to improve MSN property as carrier compared to CTAB. These MSNs were characterized using FTIR, XRD, FESEM, HRTEM and N2 adsorption/desorption. All MSNs produced have broad peaks, showing the presence of silica in amorphous form as observed by XRD while the morphology of MSN revealed the agglomeration of particles and due to parallel arrangement pores size in both for FESEM and HRTEM.